Ceremonies and medieval theater in contemporary Peru - Cajavilca Navarro, Luis (2014)
The last remnants of the medieval religious drama of Western Europe, as the history of Charlemagne and the Twelve Peers of France, and the War of Spanish Reconquista, were introduced during the domination by the Spaniards to Peru as a means to attain spiritual conquest natural and introduce and teach the Catholic religion. In the seventeenth and eighteenth centuries , the Danza de Moros y Cristianos (as it is called in Peru) becomes a popular dance that will be present in all American civic and religious official festivities will multiply the holidays throughout Spanish America , often only by indigenous natives. From the second half of the seventeenth century artistic representations begin to be exclusively in the hands of Indians and mestizos, emerging new meanings and folk art. Then appear rich mestizo artistic expressions such as cuzqueña painting or dance Moors or Christians.